The Effectiveness of ROMATIF Therapy (Mirror Therapy and Positive Affirmation) on Strength of Muscle and Self-acceptance in Post Stroke Patients - Arlinda Arsa, Putu Sintya; Fuadiati, Lie Liana; Rinawaty, Desy (Babali Publisher, 2025)
Introduction: Stroke is a neurological condition in which some brain cells die due to a disruption of cerebral blood flow caused by a blockage or rupture of blood vessels. In stroke patients, muscle weakness typically occurs on one side of the body, a condition known as hemiparesis. This condition can lead to impaired self-acceptance. This study aims to determine the effectiveness of a combined therapy, namely mirror therapy and positive affirmations, referred to as ROMATIF therapy(Mirror Therapy and Positive Affirmations). Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 35 post-stroke patients, selected using purposive sampling. The inclusion criteria were patients aged 21–74 years who were compos mentis and experiencing upper limb hemiparesis after a stroke. The instruments used in this study included a muscle strength observation sheet and a self-acceptance questionnaire. Statistical analysis was performed using the Wilcoxon test. Results: The results showed that pre- and post-treatment self-acceptance yielded an Asymp. Sig. (2-tailed) or p-value of 0.001 < α, while pre- and post-treatment muscle strength also yielded a p-value of 0.001 < α. This indicates that H1 is accepted, meaning there was a significant difference before and after ROMATIF therapy. Conclusion: Nurses can empower patients to undertake these therapies independently, promoting self-management and engagement in their care